Evaluation of the Effect of Preoperative Oral Tizanid in on the Rate of Anesthetic Consumption & Hemodynamic Changes in Tiva (Total Intravenous Anesthesia) - Shahryar Sane (Journal of Global Pharma Technology, 2017)
Objective: Materials and Methods: A double-blind clinical trial has been performed on 50 candidates for elective laparoscopic colecystectomy undergoing general anesthesia in Educational Hospital of Imam Khomeiny uromieh, Iran. 25 randomly selected patients (the case group) were given 4 mg of oral Tizanidine 90 minutes before the induction of anesthesia whereas the remaining subjects (the control group) were given placebo. Bispectral index “BIS” level before induction and after Tizanid in premedication, Induction time(Time of bispectral index “BIS” to reach 60), Mean arterial pressure and heart rate before and after induction of anesthesia, and after intubation and 10 min after peritoneal gas insufflations and   in intraoperative period and after extubation, ,and the needed Propofol & Remifentanyl  dosage were measured and recorded. Data analysis was done with T-test and Chi-squared test, using SPSS software version 19.Results: BIS level before induction and after tizanidin premedication was 91.04±1.13 & 94.56±1.82 in control and case group respectively (p valu<0.01). Induction time was 56.9±5.35 and 80.2±2.9 seconds in control and case group respectively (p valu<0.009). Average propofol & remifentanyl needed dose for anesthesia maintenance in case group was 28.95% & 33.3% less than the needed amount in the control group respectively. There is no difference in mean arterial pressure and heart rate before and after induction of anesthesia between the two groups. Variations of mean arterial pressure and heart rate after intubation and 10 min after peritoneal gas insufflations and   in intraoperative period and after extubation, were less in Tizanidine group generally. Conclusions: Using oral Tizanidine as a premedication decreased BIS level & diminished induction time of anesthesia decreased required Propofol and remifentanyl & yielded stability in mean arterial pressure and heart rate during surgery. Considering its short duration of action, Tizanidine use as a premedication is recommended for sedation and stabilization of hemodynamic responses during the operations.Keywords: Tizanidine, Hemodynamic, Propofol, Remifentanyl, BIS,  Premedication.